Flame retardant property of flax fabrics coated by extracellular polymeric substances recovered from both activated sludge and aerobic granular sludge. (1st March 2020) - Kim, Nam Kyeun; Mao, Ningtao; Lin, Richard; Bhattacharyya, Debes; van Loosdrecht, Mark C.M.; Lin, Yuemei
Abstract: In this research, extracellular polymeric substances (EPS), such as EPSflocs and EPSgranules, were successfully extracted from activated and aerobic granular sludge, respectively, and tested as bio-based flame retardant materials. Flax fabric was coated by the biopolymeric substances and its flammability was evaluated based on a vertical burning test defined in US Federal Aviation Regulation. Both EPSflocs and EPSgranules coated flax fabrics achieved the self-extinguishment due to effective char formation. In particular, the result of the EPSgranules coated sample met the aviation requirements for the aircraft interior. Moreover, the presence of carbonated hydroxyapatite was identified in EPSgranules char residue by using FTIR and XRD analysis. It can contribute to the self-extinguishing property of the fabric by enhancing char formation. Thermogravimetric analysis also demonstrated that EPSgranules coated flax was able to produce greater amount of char residue and its decomposition rate was significantly reduced. This research indicates that there is a great potential to use this biopolymer as a resource for developing high performance bio-inspired flame retardant materials and contribute to a circular economy. Graphical abstract: Image 1 Highlights: Extracellular polymeric substances (EPS) were recovered from wastewater sludge. EPS coated flax fabrics were self-extinguishing in the vertical burning test. Granular sludge EPS showed better fire performance than activated sludge EPS. Carbonated hydroxyapatite of EPSgranules led to flame retardancy of flax fabrics.